2003
DOI: 10.1002/cii.78
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between NRT-based MAPs and behaviourally measured MAPs at different stimulation rates – a multicentre investigation

Abstract: Seventeen adult subjects participated in a multicentre trial to compare the performance between an NRT-based MAP and their behavioural MAP. The NRT-based MAP was made using a correction factor to predict T/C levels, calculated from the difference between the ECAP threshold ('T-NRT') and the measured T/C levels at electrode 10, as described by Brown et al. (2000). A secondary aim was to compare T/C levels in behavioural MAPs at different stimulation rates with the predicted T/C levels in NRT-based MAPs. Perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
1
2
1
Order By: Relevance
“…Craddock et al, 2003). Thus, even though the subjects were elderly, their implant performance was comparable with other groups reported in the literature.…”
Section: Ratingsupporting
confidence: 87%
See 3 more Smart Citations
“…Craddock et al, 2003). Thus, even though the subjects were elderly, their implant performance was comparable with other groups reported in the literature.…”
Section: Ratingsupporting
confidence: 87%
“…The fact that the C levels tended to be under-rather than overestimated is an important finding in this group who may not be able to reliably articulate discomfort from over-stimulation. The overestimation of basal C levels in ACE users reported by Craddock et al (2003) was not seen for the current group. Although the deviation between behavioral and NRT based C levels indicated that NRT thresholds slightly exceeded the measured C levels in individual subjects 2, 5, and 6, this did not result in poor comfort ratings for the NRT based MAP.…”
Section: Ratingcontrasting
confidence: 77%
See 2 more Smart Citations